1979
DOI: 10.1128/jb.137.1.62-68.1979
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ethylenediaminetetraacetate on phospholipids and outer membrane function in Escherichia coli

Abstract: Treatment of Escherichia coli K-12 strain S15, containing a normal amount of phospholipase A, with ethylenediaminetetraacetate (EDTA) resulted in an increase in sensitivity of the organism to actinomycin D. Strain S17, a mutant deficient in both detergent-resistant phospholipase A and detergent-sensitive phospholipase A, was considerably less sensitive to the antibiotic after the treatment. Both strains released lipopolysaccharide after EDTA treatment, indicating that this outer membrane component alone is not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

1979
1979
1986
1986

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…Here we try to discriminate between three possible modes of colicin E2 export: release resulting from cell lysis; the specific secretion (excretion) of colicin independent of, but usually accompanied by lysis; and a semi-selective increase in membrane permeability allowing some proteins, including colicin, to leak out of the cell. The results presented support the last alternative, and we therefore examined the possibility that envelope permeability changes were caused by the activation of host cell phospholipase(s), as is known to occur upon EDTA treatment or bacteriophage infection Hardaway et al, 1975;Hardaway and Buller, 1979).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Here we try to discriminate between three possible modes of colicin E2 export: release resulting from cell lysis; the specific secretion (excretion) of colicin independent of, but usually accompanied by lysis; and a semi-selective increase in membrane permeability allowing some proteins, including colicin, to leak out of the cell. The results presented support the last alternative, and we therefore examined the possibility that envelope permeability changes were caused by the activation of host cell phospholipase(s), as is known to occur upon EDTA treatment or bacteriophage infection Hardaway et al, 1975;Hardaway and Buller, 1979).…”
Section: Introductionmentioning
confidence: 85%
“…The major E. coli K-12 phospholipase is the detergent-resistant PldA phospholipase Al-A2 (Scandella and Kornberg, 1971;Ohki et al, 1972;Nishijima et al, 1977;de Geus et al, 1983). PldA phospholipase activity is increased when cells are treated with membrane perturbants or are subjected to heat shock (Hardaway and Buller, 1979;de Geus et al, 1983, and data not shown). Direct measurements of phospholipase activity in crude cell extracts (Materials and methods) indicated a 30to 40-fold increase starting shortly before the onset of protein release and quasi-lysis, irrespective of whether the lysis gene was under the control of the colicin gene or lacZ promoters.…”
Section: Lysis Leakage or Secretion?mentioning
confidence: 91%
“…The results in this paper showed that the unshielding does not require the presence of OM phospholipase. In this respect, the action of EDTA on the OM seems to be different: it also releases LPS [23], but the OM permeability increase is reported to be dependent on the presence of OM phospholipase [7].…”
Section: Discussionmentioning
confidence: 96%
“…However, Escherichia coli mutants deficient in this phospholipase are still fully sensitive to polymyxin [16,17], BPI [11] or immune bacteriolysis [13] indicating that under these conditions the role of phospholipase is secondary. On the other hand, a phospholipase-deficient mutant was resistant to the increase of the permeability of the OM caused by EDTA, indicating that phospholipase is an important mediator in the action of EDTA on the OM [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation